The Development of the Enterprise Client-orientated Management Instruments of the Tourist Branch - Voskolovich, Nina A.; Kovaleva, Tatiana V.; Markin, Maksim I.; Demin, Sergey S.; Zinchenko, Lyudmila A. (International Review of Management and Marketing, 2016)
The study relevance of the management tendencies development in the client-orientated management in the tourism sphere is caused, first, by that the tourism is one of the most profitable and dynamically developing branches of the national economy. International experience indicates a high social and economic efficiency of tourism. However, in Russia the return from the tourist market is not comparable to indicators of the efficiency. According to foreign experts, Russia may take in a year about 40-50 million of foreign tourists per year that corresponds to receiving about 25 billion dollars of the income. Statistical data testify that now tourism is the third most profitable sector of the global economy, conceding to the oil and automotive industries, which specific weight in the world export makes 11% and 8,6% respectively. The tourism specifics consist in that it is one of the riskiest kinds of activity directly depending on economic, political and social stability in the country, existence of the developed infrastructure, tourist resources, etc. The management reform experience, accumulated in our country over the last ten years, showed that the folding system proved ineffective in solving the economy development problems and especially the problem of non-production sectors. The development of non-productive sphere and especially the tourism sector is still in the background Keywords: management, tourism, client orientation, development, instruments JEL Classifications: L82, L83, M31